STUDY OF NONENZYMATIC BROWINING DEVELOPMENT OF LOCAL SOUR ORANGE JUICE BY USING MODEL SYSTEMS 1-EFFECT OF SOLUBLE SOLIDS CONCENTRATION ON ASCORBIC ACID CONTENT AND MELANOIDINS FORMATION IN MODEL SYSTEMS OF LOCAL SOUR ORANGE JUICE DURING STORAGE - M. Al-Asuad; Mazin Al-Zuaidy; Rajab Aldosaky (Mesopotamia Journal of Agriculture)
Synthetic model systems of local sour orange juice were prepared by different concentrations 10, 30 and 50%, with different contents of some compounds (ascorbic acid, reducing sugar, amino acids) that might play a role in brown pigments formation. Samples were stored at 20, 30 and 40ْC for 4 months. Results showed that increasing temperature and period storage caused decreasing in ascorbic acid content and increasing melanoidins formation of model system. Increasing total soluble solids concentration caused decreasing in ascorbic acid degradation and melanoidins formation. The study showed that high value of melanoidins formation was noticed in model system that contained ascorbic acid. This indicated that ascorbic acid was the principle component that responsible for nonenzymatic browning development in this type of food products.